2015
DOI: 10.1007/s11883-014-0480-7
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Stenosis: From Diagnosis to Management, Where Do We Stand?

Abstract: Carotid atherosclerosis is implicated in 20-30 % of strokes. However, the annual risk of stroke in patients with asymptomatic carotid stenosis is less than 5 %. Symptomatic carotid stenosis poses a greater risk for recurrent stroke with estimates as high as 15 % per year. This paper aims to raise awareness of populations at risk for carotid stenosis, the role of carotid screening and the sensitivity and specificity of various diagnostic modalities. The results of previous trials that support current guidelines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Plaque was defined as a focal thickening ≥1.5 mm measured from the media–adventitia interface to the intima–lumen interface 22. Internal carotid artery stenosis was defined as follows: stenosis 16–50 per cent spectral broadening during all the cardiac cycle and systolic blood velocity <140 cm/s; stenosis >50 per cent as systolic blood velocity ≥140 cm/s and spectral broadening during all the cardiac cycle; occlusion as absence of Doppler signal 23. Carotid atherosclerosis was defined as the presence of plaque and/or stenosis and/or occlusion at the carotid vascular tree.…”
Section: Methodsmentioning
confidence: 99%
“…Plaque was defined as a focal thickening ≥1.5 mm measured from the media–adventitia interface to the intima–lumen interface 22. Internal carotid artery stenosis was defined as follows: stenosis 16–50 per cent spectral broadening during all the cardiac cycle and systolic blood velocity <140 cm/s; stenosis >50 per cent as systolic blood velocity ≥140 cm/s and spectral broadening during all the cardiac cycle; occlusion as absence of Doppler signal 23. Carotid atherosclerosis was defined as the presence of plaque and/or stenosis and/or occlusion at the carotid vascular tree.…”
Section: Methodsmentioning
confidence: 99%
“…First, the data comparing CAS and CEA are heterogeneous and subject to highly variable interpretations. The current literature has been used by professional societies and practitioners to both support as well as raise concern about the use of CAS for treatment of carotid stenosis 36, 37, 38, 39. Second, there are huge financial incentives at stake in the treatment of severe carotid disease.…”
Section: Lessons Learned From Carotid Artery Stentingmentioning
confidence: 99%
“…The current literature has been used by professional societies and practitioners to both support as well as raise concern about the use of CAS for treatment of carotid stenosis. [36][37][38][39] Second, there are huge financial incentives at stake in the treatment of severe carotid disease. Third, CEA and CAS have traditionally been performed by professionally distinct specialties, and this offers an opportunity to examine how physicians could collaborate to harness a new technology to optimize patient care.…”
Section: Lessons Learned From Carotid Artery Stentingmentioning
confidence: 99%
“…It is usually induced by atherosclerotic lesions, and is considered to be one of the major causes of stroke and cerebral ischemic events (CIE) [ 1 ]. Research has shown that symptomatic CAS will increase the risk of stroke, furthermore, even if the CAS is asymptomatic, it still can place an individual at more than 3% increased risk of suffering from stroke in the next year [ 2 , 3 ]. For the treatment of patients with CAS, the most important aspect is how to prevent an ischemic stroke and minimize related deaths.…”
Section: Introductionmentioning
confidence: 99%